Penggunaan Media Card-Ting Meningkatkan Pengetahuan Kader Kader Untuk Deteksi Dini Stunting - Novita Wardani; Murti Ani; Suhardono (Jurnal Kebidanan Malakbi, 2026)
Stunting is a major problem in Indonesia. Based on the results of the Indonesian Nutritional Status Study, the prevalence of stunting decreased from 24.4% in 2021 to 21.6% in 2022. The government's policy target for 2024 is 14%. The role of cadres helps raise family awareness to prevent stunting. Good cadre knowledge and skills can facilitate the dissemination of information and the practice of early detection of stunting screening. Card-Ting educational media is a stunting card containing signs of stunting (height and weight curves, bone and tooth growth, motor development). The study aims to analyze the effect of Card-Ting media on cadre knowledge and skills. The research design used a quasi-experimental with a pre-post test. The population was all village cadres in the stunting locus of Blora Regency. The sample of cadres was 60 cadres using a consecutive sampling technique. The treatment group was given stunting education using the Card-Ting module and media. Meanwhile, the control group used the module. Education was provided for 2 hours over 2 days. The first day was an explanation of stunting and the second day was practice using the Card-Ting media. The knowledge instrument used a questionnaire and the skills of Card-Ting Media practice cadres used a checklist observed for 3 months. The results of the pre-posttest analysis of knowledge and skills with a dependent t-test showed a difference before and after the value of p=0.000 (p<0.05). Statistical tests of the control and treatment groups using the Mann Whitney test showed a difference between the knowledge groups p=0.033 (p<0.05) and skills p=0.003 (p<0.05) meaning there is an effect of Card-Ting media on the knowledge and skills of cadres. Card-Ting media can help cadres carry out early detection of stunting so that appropriate preventive measures can be taken for children at risk of stunting.